2010
DOI: 10.1016/s1474-4422(10)70184-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 9p21 in amyotrophic lateral sclerosis in Finland: a genome-wide association study

Abstract: Introduction The genetic etiology of amyotrophic lateral sclerosis (ALS) is not well understood. Finland is a well-suited location for a genome-wide association study of ALS, as the incidence of the disease is one of the highest in the world, and because the genetic homogeneity of the Finnish population enhances the ability to detect risk loci. Methods We performed a genome-wide association study of 442 Finnish patients diagnosed with ALS, and 521 Finnish control subjects using Illumina genome-wide genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
188
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(196 citation statements)
references
References 33 publications
(46 reference statements)
4
188
1
3
Order By: Relevance
“…A common founder was originally proposed for Finnish FALS cases based on a 42-SNP haplotype. 8 A subsequent meta-analysis of genome-wide association study data from five European 94A_8 97A_24 96A_24 93A_6 84X_2 39X_113 32X_1 38X_3 40X_4 108X_1 33X_1 107X_6 26X_7 101A_18 107A_52 26A_12 39A_371 33A_24 40A_74 2A_111 4A_14 67A_25 115A_147 53A_109 76A_10 70A_8 118A_201 119A_17 10A_196 16A_8 58A_10 72A_5 77A_15 78A_797 Identifiers with an X contain the expanded HREM allele (highlighted in red). Digits after the underscore indicate the number of chromosomes in which the haplotype was observed.…”
Section: Uk:1 C C Gg C C T Gggt G G a C A T C C T A G T A C A T A A Amentioning
confidence: 99%
See 1 more Smart Citation
“…A common founder was originally proposed for Finnish FALS cases based on a 42-SNP haplotype. 8 A subsequent meta-analysis of genome-wide association study data from five European 94A_8 97A_24 96A_24 93A_6 84X_2 39X_113 32X_1 38X_3 40X_4 108X_1 33X_1 107X_6 26X_7 101A_18 107A_52 26A_12 39A_371 33A_24 40A_74 2A_111 4A_14 67A_25 115A_147 53A_109 76A_10 70A_8 118A_201 119A_17 10A_196 16A_8 58A_10 72A_5 77A_15 78A_797 Identifiers with an X contain the expanded HREM allele (highlighted in red). Digits after the underscore indicate the number of chromosomes in which the haplotype was observed.…”
Section: Uk:1 C C Gg C C T Gggt G G a C A T C C T A G T A C A T A A Amentioning
confidence: 99%
“…5,6 Genome-wide association studies in sporadic and familial ALS demonstrated highly significant association with single-nucleotide polymorphisms (SNPs) across a 170-Kb region at 9p21.2. [7][8][9][10][11] A massive GGGGCC hexanucleotide repeat expansion mutation (HREM) has recently been identified within intron 1 of C9ORF72 as the pathogenic mutation responsible for familial and sporadic ALS and FTD in these cases. 12,13 Here we describe HREM mutation frequencies in ALS in five European populations.…”
Section: Introductionmentioning
confidence: 99%
“…ITPR2 has a role in glutamate-mediated neurotransmission, regulation of calcium concentration and apoptosis. However, the ITPR2 association has not been found in a replication study and in subsequent GWAS (Chiò et al, 2009;Fernández-Santiago et al, 2011;Laaksovirta et al, 2010;Shatunov et al, 2010;Van Es et al, 2009c). Variation in the dipeptidyl-peptidase 6 (DPP6) gene was found to be significantly associated with sALS in a GWAS performed in a combined GWA data set from the USA and the Netherlands (Van Es et al, 2008).…”
Section: Genome Wide Association Studies In Sporadic Alsmentioning
confidence: 98%
“…Next, data of the first GWAS in FTLD-TDP were suggestive for association of five SNPs (rs774352, rs774351, rs3849942, rs2814707, rs774359) on chromosome 9p21, in the same LD block . Subsequently, a Finnish and a British independent ALS GWAS identified genome-wide significance with SNPs rs3849942, rs2814707, rs774359, rs2225389 (Laaksovirta et al, 2010) and with SNPs rs3849942, rs2814707, rs903603 (Shatunov et al, 2010) respectively, all in the same locus at chromosome 9p21. The Finnish study defined a 42-SNP haplotype associated with increased risk of ALS in the Finnish population, located in a 232 kb LD block which overlaps with the previously reported 80 kb LD block (van Es et al, 2009) and the 106.5 kb LD block of the UK study (Shatunov et al, 2010).…”
Section: Population-based Association For Als and Ftld To Chromosome 9pmentioning
confidence: 99%
“…The minimally linked region in all these families is about 3.6 Mb in size containing five known protein-coding genes. Moreover, several recent genome-wide association studies (GWAS) in ALS populations from different European origins showed the presence of a major genetic risk factor for ALS at the same chromosome 9p region (Laaksovirta et al, 2010;Shatunov et al, 2010;van Es et al, 2009). The Finnish study narrowed the associated region to a 232 kb linkage disequilibrium (LD) block containing three known genes (MOBKL2B, IFNK, C9orf72) and suggested the presence of a major risk gene with high penetrance (Laaksovirta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%